Product review on the IMD serogroup B vaccine Bexsero®. Issue 1 (31st December 2022) - Deghmane, Ala-Eddine; Taha, Muhamed-Kheir
ABSTRACT: Bexsero® is a multicomponent vaccine composed of four major proteins of Neisseria meningitidis : the fHbp, NHBA, NadA and PorA. This vaccine was licensed against invasive meningococcal disease (IMD) due to serogroup B isolates. When administered alone, Bexsero® showed a safety profile similar to other childhood vaccines. It provides an excellent immunogenicity but that requires booster doses in infants and young children. Although the vaccine does not seem to impact on acquisition of carriage of serogroup B isolates, it confers protection against isolates of serogroup B harboring distinct but cross-reactive variants of fHbp, NadA and NHBA. Primary vaccination schemes in infancy underwent a rapid increase after a toddler booster suggesting an anamnestic response and the establishment of a memory response. As Bexsero® targets sub-capsular proteins that can be conserved regardless the capsule, the vaccine can be effective against non-B isolates such as isolates of serogroups W and X.